2022
DOI: 10.1007/s41252-022-00289-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Journey Before, During and After Diagnosis of a Neurodevelopmental Condition: Suggestions from a Sample of Australian Consumers and Professionals

Abstract: Objectives The current study used a transdiagnostic approach to explore experiences of consumers and professionals on how the process of assessing and diagnosing neurodevelopmental conditions can be improved. Methods Individuals with personal and/or professional experience of this clinical pathway were invited to complete an online survey. A convenience sample of 117 Australian participants provided qualitative data describing how to improve this clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…Coaching via telehealth during the waitlist time has been demonstrated to effectively enhance parent’s utilisation of intervention strategies for challenging behaviours for toddlers awaiting diagnosis of autism, which in addition, improves caregivers’ self-efficacy and quality of life (Carey et al, 2021 ; Kunze et al, 2021 ). Once receiving a diagnosis for their child, caregivers from this study responded with confusion and high levels of stress, similar to those identified by Evans et al ( 2022 ). To address the after-effects of a diagnosis, it may be beneficial for caregivers to be offered counselling or linked to support groups to assist with their emotional processing of their child’s diagnosis (Evans et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Coaching via telehealth during the waitlist time has been demonstrated to effectively enhance parent’s utilisation of intervention strategies for challenging behaviours for toddlers awaiting diagnosis of autism, which in addition, improves caregivers’ self-efficacy and quality of life (Carey et al, 2021 ; Kunze et al, 2021 ). Once receiving a diagnosis for their child, caregivers from this study responded with confusion and high levels of stress, similar to those identified by Evans et al ( 2022 ). To address the after-effects of a diagnosis, it may be beneficial for caregivers to be offered counselling or linked to support groups to assist with their emotional processing of their child’s diagnosis (Evans et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
“…Once receiving a diagnosis for their child, caregivers from this study responded with confusion and high levels of stress, similar to those identified by Evans et al ( 2022 ). To address the after-effects of a diagnosis, it may be beneficial for caregivers to be offered counselling or linked to support groups to assist with their emotional processing of their child’s diagnosis (Evans et al, 2022 ). In addition, caregivers from this study required more detailed information from health professionals regarding their child’s condition, reason for behaviours, and strategies to best support their child.…”
Section: Discussionsupporting
confidence: 79%
“…The most commonly accessed services were medical professionals (pediatricians, child psychiatrists, general practitioners) and speech/language therapists. This aligns with the typical diagnostic journey of many families, where a general practitioner provides referral to a pediatrician for further evaluation (Evans et al, 2022; Stahmer et al, 2019), after which referral may be made to a tertiary service. In contrast, some of the least commonly accessed services were psychological services and behavioral management/skills therapies.…”
Section: Discussionmentioning
confidence: 59%
“…Consistent with research exploring other developmental and behavioral conditions (Donders, 2020;Evans et al, 2022), the reviewed evidence highlighted the benefits of feedback sessions and reports for clarifying the FASD diagnosis and guiding future strategies and supports. Caregivers particularly valued the focus on the individual's strengths along with understanding areas of vulnerability.…”
Section: Discussionmentioning
confidence: 71%